Performance Analysis of a Magnetorheological Damper with Energy Harvesting Ability - Guoliang Hu; Yun Lu; Shuaishuai Sun; Weihua Li (Shock and Vibration)
A magnetorheological (MR) damper with energy harvesting ability was proposed based on electromagnetic induction (EMI) principle. The energy harvesting part was composed of a permanent magnet array and inducing coils which move vertically. This device could act as a linear power generator when the external excitation was applied, and the kinetic energy could be converted into electrical energy due to the relative linear motion between the magnets array and the inducing coils. Finite element models of both the MR damper part and the linear power generator part were built up separately to address the magnetic flux distributions, the magnetic flux densities, and the power generating efficiency using ANSYS software. The experimental tests were carried out to evaluate the damping performance and power generating efficiency. The results show that the proposed MR damper can produce approximately 750 N damping forces at the current of 0.6 A, and the energy harvesting device can generate about 1.0 V DC voltage at 0.06 m·s−1 excitation.